Tatalaksana laser CO2 pada hiperplasia kelenjar sebasea: laporan kasus - Maylita Sari; Arisia Fadila; Muhammad Yulianto Listiawan; Bagus Haryo Kusumaputra; Irmadita Citrashanty (Intisari Sains Medis, 2022)
Background: Sebaceous gland hyperplasia is a benign skin disorder in the form of macules or papules which are generally < 1 mm in size, skin color or yellowish at the mouth of the pilosebaceous gland follicle.1 This disorder can cause cosmetic morbidity and psychosocial impacts for patients. There are various treatment modalities for sebaceous gland hyperplasia associated with the risk of pain, depigmentation, bleeding during the procedure, scarring, and recurrence. CO2 laser is one of the therapeutic approaches that are considered effective and safe. Case: A female patient came with the chief complaint of lumpy skin-colored lumps on the back of the ear to the left neck that had increased in number and had not been painful since about 4 years ago. Histopathological examination was performed on the lump showing hyperplasia of the sebaceous glands. The patient was treated with 2 CO2 Laser sessions with an even skin surface result. Observations made within 9 months after the procedure did not reveal any recurrence of the lesion. Conclusion: CO2 laser can be an effective and safe alternative therapy for sebaceous gland hyperplasia.   Latar Belakang: Hiperplasia kelenjar sebasea adalah kelainan jinak kulit berupa makula atau papula yang umumnya berukuran < 1 mm sewarna kulit atau kekuningan di muara folikel kelenjar pilosebasea.1 Kelainan ini dapat menimbulkan morbiditas kosmetik dan dampak psikososial bagi pasien. Terdapat berbagai modalitas tatalaksana hiperplasia kelenjar sebasea yang berhubungan dengan risiko nyeri, depigmentasi, perdarahan selama prosedur, skar, hingga kekambuhan. Laser CO2 merupakan salah satu pendekatan terapi yang dianggap efektif dan aman. Kasus: Pasien wanita datang dengan keluhan utama benjolan bergerombol sewarna kulit pada telinga bagian belakang hingga leher kiri yang bertambah banyak dan tidak nyeri sejak kurang lebih 4 tahun yang lalu. Pemeriksaan histopatologi dilakukan pada benjolan menunjukkan hasil hiperplasia kelenjar sebasea. Pasien diterapi dengan 2 sesi Laser CO2 dengan hasil permukaan kulit rata. Observasi yang dilakukan dalam 9 bulan paska tindakan tidak didapatkan rekurensi pada lesi. Simpulan: Laser CO2 dapat menjadi alternatif terapi pada hiperplasia kelenjar sebasea yang efektif dan aman.